Preparation of clay/pp nanocomposite by using PP-PA6 block copolymer as a compatabilizer - Chong, Timothy Wee Er. (2012)
Polypropylene (PP)/ Cloisite® 30B Montmorillonite (MMT) Clay Nanocomposites were prepared using a new PP-Nylon copolymer as a compatibilizer. A 2 step melt-compounding process with a twin-screw extruder was employed in our method. Nanocomposites with 4 weight percent loadings of MMT Clay were prepared. The purpose of this project is to investigate the feasibility of obtaining a well-exfoliated PP/Clay Nanocomposite (PPCN) with the use of the PP-Nylon compatibilizer. The dispersion of MMT Clay in our PPCNs was investigated with the X-Ray Diffraction (XRD) and Transmission Electron Microscopy (TEM). XRD and TEM results show an intercalated structure, indicating the expansion of the MMT Clay galleries after the 1st Masterbatch melt-compounding step. Further expansion of the MMT Clay galleries was not seen in the 2nd melt-compounding step. Tensile tests were also conducted on injection molded PPCN samples. Results show an increase in Elastic Modulus, and Tensile strength for all MMT clay loadings, accompanied by a reduction in ductility in the PPCNs. Thermogravimetric Analysis (TGA) show an increase in thermal stability above 3wt% MMT Clay loading. Differential Scanning Calorimetry (DSC) suggests that addition of MMT Clay additive does not have a significant effect on the crystallization behavior of PPCN.